(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objectives: To evaluate the early outcomes of single-port endoscopic nipple-sparing mastectomy combined with immediate implant-based reconstruction in patients with early-stage breast cancer. Subjects and Methods: A retrospective descriptive case-series study was conducted on 14 patients with early-stage breast cancer who underwent single-port endoscopic skin-sparing mastectomy with preservation of the nipple–areolar complex and immediate implant-based reconstruction from April 2024 to September 2024. Study variables included clinical and paraclinical characteristics, surgical outcomes, intraoperative and postoperative complications, cosmetic outcomes, and quality of life assessed using the Breast-Q questionnaire. Results: The mean age of the study population was 41.6 years. The mean BMI was 20.1 ± 1.6. The mean tumor size was 1.7 ± 0.4 cm, and most patients were classified as stage T1 (85.7%). The mean operative time was 250.5 ± 23.3 minutes, and the mean estimated blood loss was 32.2 ± 5.6 mL. No cases required conversion to open surgery. The mean postoperative hospital stay was 8.55 ± 0.6 days. Early complications included seroma formation (15%), partial nipple necrosis (7.5%), and surgical site infection (7.5%). No cases of total nipple necrosis, skin flap necrosis, or postoperative bleeding were observed. After 3 months, 78.6% of patients achieved good cosmetic outcomes according to the Lowery-Carlson scale. Breast-Q scores in the immediate reconstruction group were significantly higher than those in the non-reconstruction group. Conclusion: Single-port endoscopic nipple-sparing mastectomy combined with immediate implant-based reconstruction is a feasible and safe approach in appropriately selected patients with early-stage breast cancer. The technique provides favorable cosmetic outcomes, acceptable complication rates, and improved postoperative quality of life.